Crystal structures and gas adsorption behavior of new lanthanide-benzene-1,4-dicarboxylate frameworks - Panyarat K. (2017)
© 2017 Six new lanthanide metal organic complexes, i.e. [La 2 (NO 2 -BDC) 3 (H 2 O) 4 ] (1) [Ln(L) 0.5 (NO 2 -BDC) (H 2 O)]·3H 2 O (Ln = Eu (2), Tb (3), Dy (4) and Ho (5); L = BDC 2− or BDC 2− /NO 2 -BDC 2- ) and [Tm(NO 2 -BDC) 1.5 (H 2 O)]·H 2 O (6), have been synthesized using mixed ligands of benzene-1,4-dicarboxylic acid (H 2 BDC) and the in situ generated 2-nitro-benzene-1,4-dicarboxylic acid (NO 2 -BDC 2- ). Single crystal structures and topologies of the complexes are presented based on the single crystal X-ray diffraction and spectroscopic data. Whilst the structures of 1 and 6 contain negligible voids, the frameworks of 2–5 are microporous in nature and stable upon the removal of all the water molecules from the structures and thermal treatment to over 400 °C. Based on the study of 2, significant adsorption capacities for carbon dioxide (95 cm 3 ·g −1 or 4.2 mmol·g −1 ) and hydrogen (79 cm 3 ·g −1 or 4 mmol·g −1 ), as well as the remarkable stability of the framework upon the sorption/desorption experiments are revealed.